THE CREATIVE PROCESS OF THE SI KENYA KENA LENA DANCE WORK - Rahmadani, Rahayu; Wahyudi, Didik Bambang (ARTISTIC : International Journal of Creation and Innovation, 2023)
Teenage problems and traditional arts are attracting themes of the creation of dance works.  This creative research explores the issue of dance compositions, specifically focusing on the process involved in developing the dance work Si Kenya Kena Lena. The dance work incorporates a synthesis of notions derived from Alma Hawkins and Sumandyo Hadi. The implementation of this theory was conducted in four distinct steps, specifically preparation, organization, arrangement, and presentation. The process of creating a dance piece involves five distinct stages: sensing, valuing, envisioning, embodying, and shaping. This artistic research generates innovative dance pieces that effectively showcase the emotional upheaval experienced by teenagers in their quest for self-discovery, skillfully incorporating Sandur traditional art and East Javanese dances. The use of traditional art aspects in the creative process can generate choreography that imparts a fresh and nuanced perspective.